2008
DOI: 10.1109/tnn.2007.912300
|View full text |Cite
|
Sign up to set email alerts
|

PSECMAC: A Novel Self-Organizing Multiresolution Associative Memory Architecture

Abstract: The cerebellum constitutes a vital part of the human brain system that possesses the capability to model highly nonlinear physical dynamics. The cerebellar model articulation controller (CMAC) associative memory network is a computational model inspired by the neurophysiological properties of the cerebellum, and it has been widely used for control, optimization, and various pattern recognition tasks. However, the CMAC network's highly regularized computing structure often leads to the following: 1) a suboptima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 77 publications
0
8
0
Order By: Relevance
“…Current research is mainly focused on the convergence of the CMAC for function approximation (Lin and Chiang, 1997;Teddy et al, 2007), but our simulation showed that the convergence conditions on the learning rate of the CMAC for function approximation does not apply to the control system. Although the existing literature gave various improvements on CMAC (Cao and Tu, 2012;Cheng, 2011;Teddy et al, 2008), most of them focus on theoretical analysis and simulation. These methods still cannot meet the requirements of practical implementation of a CMAC-PD controller for electric load simulators due to the over-learning problem of the CMAC.…”
Section: Introductionmentioning
confidence: 99%
“…Current research is mainly focused on the convergence of the CMAC for function approximation (Lin and Chiang, 1997;Teddy et al, 2007), but our simulation showed that the convergence conditions on the learning rate of the CMAC for function approximation does not apply to the control system. Although the existing literature gave various improvements on CMAC (Cao and Tu, 2012;Cheng, 2011;Teddy et al, 2008), most of them focus on theoretical analysis and simulation. These methods still cannot meet the requirements of practical implementation of a CMAC-PD controller for electric load simulators due to the over-learning problem of the CMAC.…”
Section: Introductionmentioning
confidence: 99%
“…The human brain is the underlying biological structure that is responsible for human intelligence. It has complex networks of neurons which collaborate in a highly nonlinear manner to create a massive information processing systems (Teddy et al 2008). Therefore, there has always been a great interest to mimic brain-like information processing characteristics that are critical to develop such intelligent information processing systems.…”
Section: Introductionmentioning
confidence: 99%
“…However, the brain has highly complex, nonlinear, dynamic and evolutionary structure that makes it extremely difficult to model these properties. The cerebellum is one brain region located at the bottom rear of the head in which neuronal connectivity is sufficiently regular to facilitate the learning and associative memory functions and employs error correction signals to drive the network learning and memory tasks (Teddy et al 2008). However, there are several major architectural limitations are associated with cerebellar models.…”
Section: Introductionmentioning
confidence: 99%
“…Centre of Computational Intelligence undertakes active research in intelligent neuro-fuzzy systems for the modeling of complex, nonlinear and dynamic problem domains. Examples of neural and neuro-fuzzy systems developed are Modified Cerebellar Articulation Controller (MCMAC) (Ang & Quek, 2000;Teddy, Lai, & Quek, 2007;Teddy, Quek, & Lai, 2008), Generic Self-organizing Fuzzy Neural Network (GenSoFNN) , Falcon-like Fuzzy Neural Networks (Quek, Tan, & Sagar, 2001;Quah, Quek, & Leedham, 2005), RSPOP:Rough-Set based Psuedo-Outer Product Fuzzy Neural Network (Ang & Quek, 2005), TSK fuzzy neural network (Wang, Quek, & Ng, 2004;Tang, Quek, & Ng, 2005) and Pseudo Outer-Product based Fuzzy Neural Network (POPFNN) (Zhou & Quek, 1996;Quek & Zhou, 1999;Quek & Zhou, 2001;Wang et al, 2004;Singh, Quek, & Cho, 2008). These have been applied to novel and interesting applications such as automated driving (Pasquier, Quek, & Toh, 2001), signature forgery detection (Quek & Zhou, 2002), gear control for automotive continuous variable transmission (Ang, Quek, & Wahab, 2002), Bank failure and finance analysis (Tung, Quek, & Cheng, 2004;Huang, Pasquier, & Quek, 2008), medical data analysis (Tung & Quek, 2005;Tan, Quek, & Ng, 2005;Tan, Quek, Ng, & Ravzi, 2008) and fingerprint verification (Zhou, Quek, & Ng, 1995;Quek & Zhou, 2001).…”
mentioning
confidence: 99%